Transition metal-catalyzed heterocycle synthesis via C-H activation (Wiley-VCH, 2016)
As such, the text provides general mechanistic aspects and gives a comprehensive overview of catalytic reactions in the presence of palladium, rhodium, ruthenium, copper, iron, cobalt, and iridium. The chapters are organized according to the transition metal used and sub-divided by type of heterocycle formed to enable quick access to the synthetic route needed. Chapters on carbonylative synthesis of heterocycles and the application of C-H activation methodology to the synthesis of natural products are also included.